The Relationship between Diet Compliance and Blood Pressure of Hypertension Patients in Batoh Public Health Center, Lueng Bata District, Banda Aceh City - Laiyina Miska Putra; Yulia Fitri; Nunung Sri Mulyani; Silvia Wagustina (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2021)
Hypertension is an abnormal increase in blood pressure in the arteries, and the increase continuously occurs over a period. People with hypertension must consider food factors (dietary compliance) because diet is one way to lower blood pressure. Patients with hypertension should adhere to a hypertension diet so that blood pressure becomes stable and further complications can be prevented. This study aims to determine the relationship between hypertension dietary compliance and blood pressure of hypertensive patients in Batoh Public Health Center, Lueng Bata District, Banda Aceh City. This descriptive-analytic research employed a cross-sectional design. The research sample was 37 women aged 45-60 years. They were selected using a non-probability technique with the purposive sampling technique. The research was conducted at the Batoh Public Health Center, Lueng Bata District, Banda Aceh City. The research data included hypertension diet compliance and blood pressure of hypertensive patients. The level of dietary compliance was determined using a questionnaire while the level of blood pressure was determined using a digital blood pressure measurement of Tensi One. The chi-square test was employed to analyze the relationship between diet compliance and blood pressure. This study has discovered that 64.9% of hypertensive patients have non-adherent diet compliance, and 78.4% of them have high blood pressure. These results denote a significant relationship between dietary compliance and blood pressure (p-value = 0.008).